Building a High Performance Team : Proven Techniques for Effective Team Working. - Cook, Sarah, 1955- (Soft skills for IT professionals., 2009)
Building a High-Performance Team is intended to provide IT managers with informative and practical advice and tips on how to create a high-performance team.